2021
DOI: 10.1038/s41467-021-27410-5
|View full text |Cite|
|
Sign up to set email alerts
|

Serological responses and vaccine effectiveness for extended COVID-19 vaccine schedules in England

Abstract: The UK prioritised delivery of the first dose of BNT162b2 (Pfizer/BioNTech) and AZD1222 (AstraZeneca) vaccines by extending the interval between doses up to 12 weeks. In 750 participants aged 50–89 years, we here compare serological responses after BNT162b2 and AZD1222 vaccination with varying dose intervals, and evaluate these against real-world national vaccine effectiveness (VE) estimates against COVID-19 in England. We show that antibody levels 14–35 days after dose two are higher in BNT162b2 recipients wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
90
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 25 publications
(17 reference statements)
13
90
1
Order By: Relevance
“…Our followup study confirms that binding and neutralizing antibody activities induced by COVID-19 mRNA vaccines are significantly weaker in older adults at all time points following a twodose immunization series. In multivariable analyses, a higher number of chronic health conditions was also consistently independently associated with a weaker binding antibody response after two COVID-19 vaccine doses, while a longer interval between first and second vaccine doses was consistently Page 13 of 32 associated with higher binding antibody responses, as previously reported [34][35][36] . We also showed that binding antibody responses decline more rapidly over time in older adults, which can be attributed to a higher number of chronic health conditions in this group.…”
Section: Discussionsupporting
confidence: 76%
“…Our followup study confirms that binding and neutralizing antibody activities induced by COVID-19 mRNA vaccines are significantly weaker in older adults at all time points following a twodose immunization series. In multivariable analyses, a higher number of chronic health conditions was also consistently independently associated with a weaker binding antibody response after two COVID-19 vaccine doses, while a longer interval between first and second vaccine doses was consistently Page 13 of 32 associated with higher binding antibody responses, as previously reported [34][35][36] . We also showed that binding antibody responses decline more rapidly over time in older adults, which can be attributed to a higher number of chronic health conditions in this group.…”
Section: Discussionsupporting
confidence: 76%
“… 19 In the United Kingdom, a 2-dose program with a 12-wk gap between doses, predominantly with ChAdOx1-S or BNT162b2 vaccines, was reported as showing 79% reduction in risk of infection during the Alpha-dominant and 67% risk reduction during the Delta variant–dominant periods, 28 with the extended dosing schedule associated with superior VE. 25 Lopez Bernal et al 29 reported a modest reduction in VE against the Delta variant in a test-negative, case–control study in the general UK population. Direct comparisons of VE between different studies are challenging since VE wanes with time and at variable rates in different populations, and therefore, follow-up period and demographic characteristics must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…National policy mandated a 10- to 12-wk gap between first and second vaccine doses, irrespective of vaccine type. 24 , 25 …”
Section: Methodsmentioning
confidence: 99%
“…Existing evidence suggests that vaccine effectiveness increases with longer intervals between doses and, if this also applies to third doses, the administration interval will also need to be considered. 25 At the same time, it is possible that third doses will be more reactogenic than previous doses, especially if the recipient receives different vaccines for the initial and booster doses. 26 Attractive alternatives include half-dose boosters or boosting with variant-targeted vaccines, which are both under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…For the United Kingdom and countries with administration intervals that are longer than the licensed interval, another important consideration is that the extended interval of 8 to 12 weeks between vaccine doses provides higher serologic responses and increased vaccine effectiveness than the licensed interval of 3 to 4 weeks for mRNA vaccines, 25 which may provide the populations in these countries with better, longer-term protection. 12 This hypothesis is supported by our current findings comparing short and long administration intervals among persons 80 years of age or older.…”
Section: Discussionmentioning
confidence: 99%